Impact of khat (Catha edulis) and oral contraceptive use on telomerase levels and tumor suppressor genes p53 and p21 in normal subjects and breast cancer patients - Fairooz Atroosh; Molham AL-Habori; Ekram Al-Eryani; Riyadh Saif-Ali (Scientific Reports, 2024)
Abstract This study aimed to evaluate the effects of oral contraceptive (OC) use, khat chewing, and their combined effect on telomerase level and tumor suppressor genes, p53 and p21 in breast cancer (BC) patients and normal volunteers. 140 Yemeni women aged 25–40 years old enrolled, 60 newly diagnosed pretreated BC patients, and 80 control subjects. Venous blood (5 ml) was collected and the results showed BC patients to have significantly raised levels of telomerase, p53, and p21 compared to the control group. The use of OCs significantly raised telomerase in control group with no effect in BC patients; whereas p53 and p21 were significantly increased in BC patients. On the other hand, khat chewing significantly increased p53 in controls and BC patients, whereas p21 was significantly raised in BC patients. The combined use of OCs and khat chewing significantly increased telomerase and p53 in control group, and significantly increased p53 and p21 in BC patients. Telomerase was shown to be a risk factor (OR 4.4) for BC, and the use of OCs was a high-risk factor for increasing telomerase (OR 27.8) in normal subjects. In contrast, khat chewing was shown to be protective (OR 0.142), and the combined use of OCs and khat chewing decreased the risk factor of telomerase from OR 27.8 to 2.1.